(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Hemocolitis syndrome in children is a serious pathology associated with inflammatory processes in the intestine and activation of the immune response. The present study analyzes the immune mechanisms involved in the development of acute diarrheal syndrome with hemocolitis in children aged 6 months to 7 years. The studied indicators of the nonspecific immune response and cytokine profile reveal significant changes in both pro-inflammatory and anti-inflammatory mechanisms. The results obtained demonstrate the activation of the inflammatory process in children with hypertension and may be useful for the development of new approaches to therapy.